Ultrasonically assisted conversion of uranium trioxide into uranium(vi) intrinsic colloids. Issue 33 (4th August 2021) - Cot-Auriol, Manon; Virot, Matthieu; Micheau, Cyril; Dumas, Thomas; Le Goff, Xavier; Den Auwer, Christophe; Diat, Olivier; Moisy, Philippe; Nikitenko, Sergey I.
Abstract : 20 kHz sonication of amorphous and crystalline UO3 powder in pure water under Ar/(10%)CO atmosphere yields intrinsic uranium(vi ) colloids exhibiting a schoepite-like crystallographic structure. Abstract : Under oxidizing conditions, the corrosion of spent nuclear fuel may lead to the leaching of radionuclides including soluble uranyl-based species. The speciation of the generated chemical forms is complex and the related potential formation of colloidal species appears surprisingly poorly reported in the literature. Their formation could however contribute significantly to the mobility of radionuclides in the environment. A better knowledge in the speciation and reactivity of these species appears particularly relevant. This study describes the preparation and characterization of intrinsic uranium(vi ) colloids from amorphous and crystalline UO3 in pure water assisted by 20 kHz ultrasound. In the presence of carbon monoxide preventing the sonochemical formation of hydrogen peroxide, ultrasonic treatment boosts the conversion of UO3 powder into ( meta -)schoepite precipitates and yields very stable and notably concentrated uranium(vi ) nanoparticles in the liquid phase. Using HR-TEM, SAXS and XAS techniques, we confirmed that the colloidal suspension is composed of quasi-spherical nanoparticles measuring ca. 3.8 ± 0.3 nm and exhibiting a schoepite-like crystallographic structure. The proposed method demonstrates the possible formation of environmentally relevant U(vi ) colloidal nanoparticles appearing particularly interesting for the preparation of reference systems in the absence of added ions and capping agents.